Learning Effectivenss of Blended Learning in Higher Education Context - Christiana Sidupa (Universitas Sembilanbelas November Kolaka, 2019)
The notion of applying ICT to support traditional learning approach (face-to-face learning) is obviously not new todays. This study aimed to seek the significant difference between the mid test and final test scores of students’ English listening and reading skills. Mid test score represents face-to-face learning approach applied from first meeting whereas final test score represents blended learning approach employed after the mid test. The method used in this study was quantitative. A random selection of samples was carried out involving 133 first year undergraduates in Jakarta pursuing English as a compulsory course. Data collection technique used mid and final tests of two English skills: listening and reading. This study revealed that there was a significant difference between the mid test and the post test scores.